Analysis of Design and Material Selection of a Spur gear pair for Solar Tracking Application. (2018) - Gupta, Krishanu; Chatterjee, Sushovan
Abstract: The principal intentions of this paper are geometrical modelling and computational study of different static stresses on spur gears of different materials for an indigenous mechanical solar tracker. The analyzed static stress results of the symmetric type involute profiled gear pair are compared on the basis of the material and the best result is selected for the application in the tracker mechanism. Providing importance on the non- renewable energy sources, solar energy is the major primary source of energy which can satisfy the human needs for the future. Gear operated mechanical Solar Tracking System is cheaper, require less skilled worker, easy to maintain and can be placed at hilly areas, remote or dusty or rainy place to help electrical power deficiency in rural areas and also can be installed easily in educational institutions, big offices, etc., which can save non-renewable sources of electrical energy for future use. The gears are one of the most imperative and crucial component in a mechanical power transmission unit, and its robustness led to the choice as mechanical component in the tracking mechanism. Since, the system is open to environment; therefore, the material selection of the gears becomes an important issue.